SOCIALIZATION OF FINANCIAL MANAGEMENT IN MSMEs ARENTA IN PANDEGLANG DISTRICT - BANTEN - azizi, Enji; Nurhikmat, Mira; Yulaikah, Yulaikah; Wirasmara Kusuma, Hero; Astuti, Peni (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
In the Indonesian economy, UMKM is the business group with the largest number and proved to be able to withstand various types of economic crises. The number of UMKMs increases from year to year. The new development of the UMKM can only be seen from the number side. In general, especially in the financial aspect, only a few UMKMs have experienced development in terms of their financial performance. This is not apart from the unconsciousness of UMKM’s perpetrators about the importance of corporate finance management. Financial management becomes one of the important aspects of the company’s progress. Financial management can be done through accounting. Accounting is a systematic process for generating financial information that can be used for decision-making for its users. Method of implementation: 1. Problem-solving (Preliminary Studies, Identification, and Formulation of Problems, Problem Solving), 2. Khalayak Target (According to the outcome of the problem that the author has previously outlined, the target audience in this service is the financial manager on UMKM ARENTA 3. Keterkaitan (For Society: Increasing knowledge about good and correct financial management, For the place of service to the community: Giving an active role of the community in the management of UMKM finance, for the institution of the University of Faletehan: Implementing tasks as a lecturer is the Three Darma College is from the aspects of devotion to society